Development of models to predict product deposition from coverage obtained on artificial collectors and their practical applications - Garcerá, Cruz; Moltó, Enrique; Chueca, Patricia (2017)
Models to relate the observed coverage on artificial collectors used in field tests (water-sensitive paper, WSP) and in laboratory bioassays of citrus pests (pieces of polyvinyl chloride sheets, PVC) with product deposition are described. Different solutions of plant protection products commonly used for pest control in citrus were sprayed in a Potter Tower on PVC and WSP under the same controlled conditions. These experiments led to the formulation of different basic models to relate coverage and deposition depending on the products and collectors. The best fitting model was selected from among those that had highest coefficients of determination (R-2) and lowest estimation error (RMSEP), and at the same time resulted in a normal distribution of residuals. Finally, coverage on pieces of PVC sheets was related with coverage obtained on WSP by different equations depending on the product being applied. Such equations can be used to link laboratory and field results in order to assess the quality of a spray application in citrus cultivation.